CEO Shareholdings and Earnings Manipulation: A Behavioral Explanation - Petrou, Andreas; Procopiou, Andreas (My University, 2016)
Empirical findings on the relationship between CEO shareholdings and earnings manipulation are inconclusive. In response, this study attempts to shed more light by suggesting that this relationship is influenced by situational contingencies that affect CEO perceptions of the costs and benefits associated with earnings manipulation. To support this perspective we draw on the prospect theory and the approach/inhibition theory of power to examine the relationship between CEO shareholdings and earnings manipulation in light of CEO power. We test this relationship on a sample of 16,873 observations from 2,257 US public firms. Findings show that increasing CEO shareholdings has a negative effect on earnings management, and on re-statements due to irregularities, and that duality positively moderates these relationships. The findings contribute to the corporate governance practice since they have implications for the design of CEO remuneration packages.
Keywords: Agency theory; CEO shareholdings; Corporate governance; Earnings management; Irregularities